Clinical Chemistry Biomarker Profiles of Mothers with Stunted Children in Bone Bolango Regency - Deby Sinta Darise; Ni luh Arwati; Srikit S. Nurkamiden (Fakultas Kesehatan Masyarakat, Universitas Pancasakti, Makassar, 2025)
Maternal nutritional status plays a crucial role in child health and development, particularly in relation to stunting. This study aimed to describe the biochemical nutritional profile—including total protein, albumin, globulin, and lipid levels—of mothers with stunted children in Bone Bolango Regency. A descriptive design was employed with 26 mother-child pairs (aged 2–4 years) from Ayula Selatan and Dunggala Villages in September 2024. Blood samples were analyzed at the Integrated Health Laboratory of FSTIK UBMG. The mean values of maternal biomarkers were: total protein (4.5 g/dL), albumin (3.0 g/dL), globulin (1.5 g/dL), total cholesterol (202 mg/dL), triglycerides (165 mg/dL), HDL (63 mg/dL), and LDL (106 mg/dL). These findings suggest that suboptimal maternal biochemical nutritional status may contribute to the risk of stunting in children.